2007
DOI: 10.1007/s11145-007-9058-x
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of second and third grade dysfluent urban readers

Abstract: This study examined the heterogeneity within a sample of 140 urban second and third graders identified as at-risk for reading failure due to inefficient word and/or nonword reading. Cluster analyses were conducted using standardized factor scores from a four-factor structural equation model characterizing reading performance in this sample. These standardized factor scores represented performance on four distinct factors: efficiency of word-level skills, text level skills, decoding, and vocabulary. Results ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…According to Lovett, accuracy is developed first via the application of phonological decoding skills and the use of context, and fluency of word reading develops second. Furthermore, in a previous study (Pierce, Katzir, Wolf, & Noam, 2007), our findings showed that a large proportion of this urban, dysfluent sample demonstrated untimed decoding scores (Word Attack) in the average range, offering further evidence that timing and word-level decoding emerge separately in this population. Future research will need to examine which instructional methods are most effective at promoting efficiency of word identification (see Wolf, Miller, & Donnelly, 2000).…”
Section: Discussionsupporting
confidence: 75%
“…According to Lovett, accuracy is developed first via the application of phonological decoding skills and the use of context, and fluency of word reading develops second. Furthermore, in a previous study (Pierce, Katzir, Wolf, & Noam, 2007), our findings showed that a large proportion of this urban, dysfluent sample demonstrated untimed decoding scores (Word Attack) in the average range, offering further evidence that timing and word-level decoding emerge separately in this population. Future research will need to examine which instructional methods are most effective at promoting efficiency of word identification (see Wolf, Miller, & Donnelly, 2000).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, we are working to understand the potential of RAVE‐O to address the multiple issues of children with comorbid reading and social‐emotional challenges. Toward these ends, we (Pierce, Katzir, Noam, & Wolf, 2007) are studying RAVE‐O along with a resiliency program (Noam, Winner, Rhein, & Molad, 1996) in an after‐school setting with this population. Furthermore, future analyses will focus on differential treatment outcomes for subtypes of impaired readers.…”
Section: Efficacy Of Rave‐omentioning
confidence: 99%
“…While word reading and oral language comprehension are two necessary components for successful reading comprehension as hypothesized by the simple view of reading 1 (Catts, Hogan, & Adlof, 2005;Hoover & Gough, 1990;Kirby & Savage, 2008), achieving automaticity in word reading is an essential requirement for reading comprehension (Adams, 1990;Chall, 1996;Fuchs, Fuchs, Hosp, & Jenkins, 2001;Perfetti, 1985Perfetti, , 1992Stanovich, 1980). It has been shown that word decoding accuracy and efficiency are two separate constructs for low-performing second and third grade students (Pierce, Katzir, Wolf, & Noam, 2007). As individuals have a limited amount of attentional resources available for any given cognitive tasks, the greater the amount of attention paid to word decoding, the less is available for meaning construction.…”
Section: Introductionmentioning
confidence: 99%